Disease evolution in mixed connective tissue disease: results from a long-term nationwide prospective cohort study - Reiseter, Silje (Arthritis Res Ther, 2017)
BACKGROUND: The phenotypic stability of mixed connective tissue disease (MCTD) is not clear, and knowledge about disease activity and remission is scarce. We aimed to establish the occurrence of evolution from MCTD to another defined rheumatic condition, and the prevalence and durability of remission after long-term observation. METHODS: In this large population-based prospective observational MCTD cohort study (N = 118), disease conversion was defined by the development of new auto-antibodies and clinical features compliant with another well-defined rheumatic condition. Remission was defined by a combination of systemic lupus erythematosus disease activity index 2000 (SLEDAI-2 K) of 0 and European League Against Rheumatism scleroderma trials and research (EUSTAR) activity index <2.5. Predictors of phenotypic stability and disease remission were assessed by logistic regression. RESULTS: Among 118 patients, 14 (12%) developed another well-defined rheumatic condition other than MCTD after mean disease duration of 17 (SD 9) years. Puffy hands predicted a stable MCTD phenotype in univariable regression analysis (OR 7, CI 2–27, P = .010). Disease activity defined by SLEDAI-2 K, decreased gradually across the observation period and > 90% of patients had EUSTAR activity index <2.5. There were 13% patients in remission throughout the whole mean observation period of 7 (SD 2) years. The strongest predictor of remission was percentage of predicted higher forced vital capacity. CONCLUSIONS: Our results strengthen the view of MCTD as a relatively stable disease entity. Long-term remission in MCTD is not frequent; however, the low SLEDAI-2 K and EUSTAR scores during the observation period suggests that the disease runs a milder course than systemic lupus erythematosus and systemic sclerosis. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13075-017-1494-7) contains supplementary material, which is available to authorized users.